In search of Edgar Allan Poe [videorecording (DVD)] : meet the man behind the myth - Kaplan, Andrew D.; Synowiec, Paul (East Rock Films, 2025)
A definitive documentary that explores the triumphant but tragic story of the brilliant poet, master short story writer, and influential critic Edgar Allan Poe. It recounts how he invented the detective story, pioneered science fiction, and shaped the horror tale, yet was plagued by alcohol, lost love, and a penchant for self-destruction. The film sheds new light on the mysterious circumstances surrounding Poe's death and his enduring influence on later writers.